Jewish Education - Kelman, Ari Y., 1971- (Rutgers University Press, 2024)
No detailed description available for ""Jewish Education"".
Description based upon print version of record.
Keywords: Judaism -- Study and teaching.; Jews -- Education.; Jewish religious education.; Judaïsme -- Étude et enseignement.; Juifs -- Éducation.; Éducation religieuse juive.; SOCIAL SCIENCE / General